Pengaruh Penggunaan Aplikasi Quizizz Mobile terhadap Motivasi Belajar Siswa di Era Pembelajaran Digital - Fathira Alifa Ahsan; Nazwa Ali Nasution; Tania Dwi Dermawan; Muhamad Alda (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital technology has promoted the use of mobile-based learning applications as supportive tools in the learning process. One widely used application is Quizizz Mobile, which provides interactive, game-based quizzes to engage students in learning activities. This study aims to examine the effect of using the Quizizz Mobile application on students’ learning motivation during the digital learning period. The research adopts a quantitative approach with an associative analytical survey design. The sample consists of 33 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire to measure students’ perceptions and motivation levels. The collected data were analyzed using descriptive statistics, percentage analysis, and simple linear regression techniques. The results show that the use of Quizizz Mobile has a positive and statistically significant influence on students’ learning motivation. Students reported higher interest, engagement, and enthusiasm when learning activities were conducted using the application. Based on these findings, Quizizz Mobile can be considered an effective digital learning medium that supports interactive learning and enhances students’ motivation, particularly in technology-based learning environments.